2016
DOI: 10.9721/kjfst.2016.48.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the inflammatory process and interaction of THP-1 monocytes with intestinal epithelial cells by glasswort (Salicornia herbacea L.) extracts

Abstract: The glasswort is an edible halophyte demonstrating various physiological effects including anti-inflammatory activity. In the present study, the effects of glasswort extracts on inflammatory events and interactions of THP-1 monocytes with intestinal epithelial cells were investigated. Five solvent fractions, including the ethylether fraction (Fr.E), were prepared from a 70% methanol extract of glasswort. THP-1 monocytes underwent differentiation by phorbol 12-myristate 13-acetate treatment and were then activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Compounds such as salbige A and salbige B which have been isolated from the aerial plant parts of the species exhibited antiproliferative activities, while pheophorbide possessed inhibitory activity against A549 and HepG2 cancer cells (Zhao et al, 2014). Dicaffeoylquinic acid derivatives and flavonoid glucosides have been attributed with several health promoting bioactivities due to their high antioxidant potency, including neuroprotective, anti-inflammatory, antiadipogenic, hepatoprotective, skin whitening, antihypelipidemic and antibacterial effects (Choi, Kang, & Hong, 2016;Essaidi et al, 2013;Kim, Jun, & Kim, 2014;Tuan et al, 2015). Moreover, Ksouri et al (2012) has reported biological effects such as hepatoprotective properties and inhibitory effects against oxidation-induced cellular damage, as well traditional medicinal uses against constipation, diabetes, obesity and cancer.…”
Section: Health Effectsmentioning
confidence: 99%
“…Compounds such as salbige A and salbige B which have been isolated from the aerial plant parts of the species exhibited antiproliferative activities, while pheophorbide possessed inhibitory activity against A549 and HepG2 cancer cells (Zhao et al, 2014). Dicaffeoylquinic acid derivatives and flavonoid glucosides have been attributed with several health promoting bioactivities due to their high antioxidant potency, including neuroprotective, anti-inflammatory, antiadipogenic, hepatoprotective, skin whitening, antihypelipidemic and antibacterial effects (Choi, Kang, & Hong, 2016;Essaidi et al, 2013;Kim, Jun, & Kim, 2014;Tuan et al, 2015). Moreover, Ksouri et al (2012) has reported biological effects such as hepatoprotective properties and inhibitory effects against oxidation-induced cellular damage, as well traditional medicinal uses against constipation, diabetes, obesity and cancer.…”
Section: Health Effectsmentioning
confidence: 99%